2016
DOI: 10.4049/jimmunol.1502410
|View full text |Cite
|
Sign up to set email alerts
|

The Microtubule-Associated Protein Lis1 Regulates T Lymphocyte Homeostasis and Differentiation

Abstract: The microtubule-associated protein Lissencephaly 1 (Lis1) is a key regulator of cell division during stem cell renewal and differentiation. In this study, we examined the role of Lis1 in T lymphocyte homeostasis and fate diversification in response to microbial infection. T cell-specific deletion of Lis1 resulted in depletion of the peripheral CD4+ and CD8+ T lymphocyte pool, owing to a loss of homeostatic, cytokine-induced proliferation. By contrast, cognate antigen-triggered proliferation was much less affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 41 publications
7
15
0
Order By: Relevance
“…As previously reported in a similar conditional knockout model (34), the deletion of LIS1 led to a dramatic decrease of peripheral CD4+ and CD8+ T cells numbers (Figure 3 – Figure Supplement 1D). This defect was previously imputed to a reduced ability of CD4+ and CD8+ T cells to proliferate in response to cytokine-driven homeostatic signals (34).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…As previously reported in a similar conditional knockout model (34), the deletion of LIS1 led to a dramatic decrease of peripheral CD4+ and CD8+ T cells numbers (Figure 3 – Figure Supplement 1D). This defect was previously imputed to a reduced ability of CD4+ and CD8+ T cells to proliferate in response to cytokine-driven homeostatic signals (34).…”
Section: Resultssupporting
confidence: 85%
“…The maturation of DP thymocytes into TCR hi CD4 SP thymocytes occurred also normally in Cd4-Cre Lis1 flox/flox mice expressing a fixed MHC class II-restricted ab-TCR transgene (AND), suggesting that LIS1 is not essential for positive selection (Figure 3 -Figure Supplement 1C). As previously reported in a similar conditional knockout model (34), the deletion of LIS1 led to a dramatic decrease of peripheral CD4+ and CD8+ T cells numbers (Figure 3 -Figure Supplement 1D).…”
Section: Lis1 Is Required For Tcr-mediated Proliferation In Cd4+ T Ce...supporting
confidence: 85%
See 1 more Smart Citation
“…The microtubule reassembles and contributes to mitotic spindle formation during cell division. Therefore, as a microtubuleassociated protein, Lis1 is also reported to regulate cell division and expansion (17,18,42). Using sequential EdU-BrdU pulsing, we have definitively demonstrated that Lis1 deficiency led to a GC B cell cycle blockade at the G 2 /M phase.…”
Section: Discussionmentioning
confidence: 75%
“…They regulate the polarized secretion of effector molecules and contribute to the maintenance of F-actin-dependent structures (15)(16)(17). Also microtubules are highly plastic and dynamic structures and orchestrated by microtubule-stabilizing and destabilizing proteins including microtubules-associated proteins (MAPs), Lissencephaly 1 (Lis1), stathmin, and tau protein (18)(19)(20). Interesting, Lis1-deficient murine models show a reduction in the number of both CD4 + and CD8 + lymphocytes in the periphery and aberrant CD8+ differentiation into long-lived memory cells suggesting that Lis1 controls homeostasis of T lymphocytes (18).…”
Section: Cytoskeleton Is Involved In the Regulation Of Crucial Cellular Processes Of Ptcl Biologymentioning
confidence: 99%